An aggressive central giant cell granuloma in a pediatric patient: case report and review of literature - Yiqiao Wang; Andre Le; Dina El Demellawy; Mary Shago; Michael Odell; Stephanie Johnson-Obaseki (Journal of Otolaryngology - Head and Neck Surgery)
Abstract Background Central giant cell granulomas are benign tumours of the mandible, presenting in children and young adults. Divided into non- and aggressive subtypes, the aggressive subtype is relatively rare and can occasionally progress rapidly, resulting in significant morbidity. Case presentation We present a case of an aggressive central giant cell granuloma (CGCG) in a six year-old female. The lesion originated in the right mandibular ramus and progressed rapidly to involve the condyle. Diagnosis was made using a combination of imaging and pathology. A timely en bloc resection of the hemi-mandible was performed with placement of a reconstructive titanium plate and condylar prosthesis. Conclusion Our case demonstrates the importance of considering CGCG in the differential diagnosis of rapidly progressive mandibular lesions in the pediatric population. Prompt diagnosis and management can greatly improve long-term outcomes.